Migration and summer destinations of humpback whales (Megaptera novaeangliae) in the western South Atlantic Ocean - Zerbini, Alexandre N.; Andriolo, Artur; Heide-Jorgensen, Mads Peter; Moreira, Sergio C.; Pizzorno, Jose Luis; Maia, Ygor G.; Vanblaricom, Glenn R.; DeMaster, Douglas P. (J. Cetacean Res. Manage., 2020)
Southern Hemisphere humpback whales (Megaptera novaeangliae) migrate from wintering grounds in tropical latitudes to feeding areas in the Antarctic Ocean. In 2003 and 2005, satellite transmitters were deployed on humpback whales on their wintering grounds off the eastern coast of South America (Breeding Stock A). Seven whales were tracked for a period of 16 to 205 days travelling between 902 and 7,258km. The tracks of these whales provided partial or full information on the migratory schedule, migration routes and location of the feeding ground in the Southern Oceans. Whales departed from the coast of Brazil from late October to late December between 20˚ and 25˚S and gradually moved away from the South American coast as they moved towards high latitudes. They followed a somewhat direct, linear path, with an approximate geographic heading of 170˚. Satellite telemetry data indicated that the migratory corridors are restricted to a relatively narrow (~500–800km) strip in the South Atlantic Ocean. Migration speed to the feeding grounds averaged 80.2km/day and lasted from 40–58 days. Four individuals arrived at the feeding ground located to the north of the South Sandwich Islands, where they were tracked up to 102 days. Movements in this area were erratic at a mean travelling speed of 22.3km/day. Satellite telemetry data indicate that the main feeding grounds for the population wintering off eastern South America lie between 22˚W and 33˚W and in the southern South Atlantic Ocean south of the Antarctic Convergence but north of 60˚S. This is only partially consistent with the currently proposed stock boundaries for this population on the feeding grounds.